Clariant and Tiangang receive go-ahead to build stabilizers JV plant in China. Issue 2 (February 2018) - Unknown
Abstract : Joint venture partners Switzerland's Clariant and Tiangang Auxiliary, a privately owned Chinese producer and supplier of light stabilizers, have received permission to purchase a site within the Cangzhou National Coastal-Port Economy and Technology Development Zone in China's Hebei province. The duo intends to invest a multi-million Swiss francs sum to construct a world-class production facility at the location for the joint manufacture of process and light stabilizers to support growing demand for high-end solutions from the region's expanding industries.